Structural evolution and hydrogen storage performance of Mg3LaHn (n = 9–20). (8th February 2022) - Zhang, Lili; Jin, Siyu; Ren, Mengxue; Lu, Cheng; Peng, Feng; Gutsev, Gennady L.
Abstract: The magnesium-lanthanum-hydrogen systems possess the goodish stability and high hydrogen storage capacity, which make them perspective as commercial Mg-based hydrogen storage materials. The exploration of these intriguing properties evolving from small atomic and molecule cluster to bulk phase are, to our knowledge, the longstanding challenge. Here, we perform a theoretical study on the structural and electronic properties of Mg3 LaH n (9 ≤ n  ≤ 20) clusters by using the Crystal Structure AnaLYsis by Particle Swarm Optimization method combined with density functional theory calculations. It is found that Mg3 LaH15 is the most stable cluster in the series, with hydrogen storage capacity of 6.6 wt% and adsorption energy of 2.76 eV. The present results offer new insights for the design and synthesis of novel hydrogen storage materials in the future. Graphical abstract: Image 1 Highlights: Structural and electronic properties of Mg3 LaHn (n = 9–20) clusters are studied. The Mg3 LaH15 is the most stable cluster with the HOMO-LUMO gap of 5.19 eV. The Mg3 LaH15 can serve as prospective material for hydrogen storage.